PERSEPSI GURU SEKOLAH DASAR TERHADAP REFORMASI KURIKULUM MERDEKA BELAJAR - SELY FIKRIYAH; Mustofa; Akhwani; Afib Rulyansah (STKIP Subang, 2026)
This study aims to examine elementary school teachers' perceptions of the Kurikulum Merdeka (Freedom to Learn Curriculum) reform and to explore the challenges encountered during its implementation. A descriptive qualitative approach was employed, involving six teachers from SD Bahrul Ulum Surabaya and SDN Krembangan Selatan I Surabaya as informants. Data were collected through semi-structured interviews covering six aspects, namely educational goals, learning materials, learning experiences, teaching strategies, implementation challenges, and assessment systems, then analyzed using the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing. Data credibility was maintained through member checking, peer debriefing, and confirmability. The findings show that teachers generally hold a positive perception of Kurikulum Merdeka, viewing it as flexible, student-centered, and oriented toward strengthening character alongside 21st-century competencies in line with the Pancasila Student Profile. Learning materials were considered simpler and more contextual, while project-based and differentiated learning strategies were reported to increase student engagement. However, teachers identified persistent obstacles, including limited facilities, heavy administrative workload, diverse student abilities, and parents' mindset that remains oriented toward numerical scores. The assessment system, comprising diagnostic, formative, and summative assessment, was perceived as providing a more comprehensive picture of student development. Keywords: Teacher Perception, Kurikulum Merdeka, Curriculum Reform, Elementary School